Implementasi Sistem Otentikasi Dokumen Berbasis Quick Response (QR) Code dan Digital Signature - Antika Lorien; Theophilus Wellem (Ikatan Ahli Informatika Indonesia (IAII), 2021)
The authenticity and integrity of documents are essential in data exchange and communication. Digital documents must be verifiable for their authenticity and integrity by all parties that use the documents. Generally, digital documents can be authenticated by using digital signatures. This study aims to implement a document authentication system based on Quick Response (QR) code and digital signature. As the case study, the document authentication system is implemented to generate digital signatures for student’s certificate documents. Furthermore, the system can also verify the authenticity of the certificate documents. Creating a digital signature requires a hash function algorithm for generating the message digest of the document. In addition, an algorithm to generate the public key and the private key used in the encryption/decryption of the message digest is also needed. The hash function utilized in this study is the Secure Hash Algorithm-256 (SHA-256), while the algorithm used for encryption/decryption is the Rivest-Shamir-Adleman (RSA) algorithm. The system is evaluated by verifying 30 student certificate documents, of which 15 of them were certificates with QR code signature generated by the system and the other 15 were certificates with QR code signature generated using a random QR code generator. The system’s testing results demonstrate that the system can ensure the authenticity and integrity of the signed certificate documents to prevent document falsification. All documents that contain random QR codes were correctly identified as false documents.